Analiza visokotlačnega in nizkotlačnega vračanja izpušnih plinov v tlačno polnjenem dizelskem motorju - Hribernik, Aleš (Strojniški vestnik, 2004)
Exhaust-gas recirculation (EGR) is an effective way of reducing NOx emissions.Two different strategies can be applied when using EGR in a turbocharged diesel engine. The first one is known as low-pressure EGR, where a passage is provided enabling exhaust gasses from below the turbine to pass to the fresh-air side of the engine. Its alternative is high-pressure EGR. In this EGR configuration the exhaust gas is withdrawn from the exhaust manifold above the turbine and fed to the intake manifold below the compressor. The applications of both strategies to a four-cylinder diesel engine were studied by means of a one-dimensional simulation. The possible range of EGR applications for both concepts and their effects on the engine and turbocharger operations were examined and are discussed in this paper.
Keywords: motorji ZNZ; recirkulacija izpušnih plinov; emisije NOx; meritve; simuliranje; izpušni plini; recirkulacija; dizelski motorji